A bibliometric analysis of river restoration - Survilė, Oksana; Kalibatienė, Diana (International Conference “Environmental Engineering”, 2023)
Increasing environmental pollution and human intervention in nature today require the restoration, study, and monitoring of the positive effects on water quality in the restored rivers. Consequently, the main research questions arise: what are the main trends in river restoration impacting water quality and the watershed ecosystem? How does it contribute to the sustainable development of the environment? To answer these questions, this paper presents the results of the bibliometric analysis of papers from the Web of Science database and a keyword map of water quality in the restored rivers. The results of this study will help scientists and practitioners to monitor the restoration of the river ecosystem and its impact on water quality, and to choose further directions of river exploitation activity.